Organisational manoeuvres for exploring and exploiting external knowledge. (1st January 2012) - Rössing, Inga; Kaiser, Stephan
The present paper explores how organisations pursue explorative and exploitative learning when using highly skilled dependent or independent contractors as external knowledge workers. It investigates why and how organisations balance stable exploitative and flexible explorative relationships with contractors, and examines the factors that influence this balance. To do this, it develops a conceptual framework that represents organisational manoeuvres for explorative and exploitative learning in the context of boundary-spanning organisational learning. The findings presented herein are based on a qualitative empirical analysis of engineering and IT areas across seven industries, and show that the exchange of existing contractors for new ones leads to a restructuring of the contractor portfolio of the firm. Further, this exchange process can be considered to be an experimental practice that results in organisational learning between exploitation and exploration.